Dam monitoring network and deformation studies - Setan, Halim; Idris, Khairulnizam M. (2004)
Deformation of concrete dam is a complex process. For large deformation structures such as concrete dam, one should consider the interaction between the structure and the underlying soil and rock strata, influence water load on the structure and the foundation rock. Safety of dams depend on the proper design, construction and monitoring of actual behavior during the construction and during the operation of the structure. This paper describes the methodology applied in deformation monitoring network, using two dimensional survey network. In this paper, the configuration of the monitoring survey network and observations within the network are given. The observation involved two-epoch data set. The adjustment of separate epochs and the localization of movements between epochs are outlined. Finally, recommendations on methodology are given. This methodology are generally applicable to any situation in which movement are to be monitored by means of a survey network.